PATHOPHYSIOLOGY OF POSTOPERATIVE STRESS REACTION AND MODERN APPROACHES TO NUTRITIVE SUPPORT FOR CHILDREN IN POSTOPERATIVE PERIOD - P.V. Shumilov; L.E. Tsypin; Yu.G. Mukhina (Педиатрическая фармакология)
Enteral nutrition is a method best adjusted to human physiology for correcting disorders of homeostasis in the postoperative period. Untimely and inadequate correction of these disorders may fatally affect a child’s health and rates of the child’s further development. Understanding the laws of stress response generation is important in selecting an optimal nutritive support in the postoperative period. It is necessary to take account of neuro-endocrine-immune response, changing metabolism and an impaired function of the gastrointestinal tract. Modern methods of diagnostics and treatment make it possible to resolve most of the arising issues, but it requires physicians to take a comprehensive approach and have knowledge in many areas of theoretical and practical medicine. Key words: stress, metabolism, children, enteral nutrition. (Pediatric Pharmacology. – 2010; 7(3):36-45)